Correction: Kornet, M.M.; Müller, T.J.J. Recent Advances in Sequentially Pd-Catalyzed One-Pot Syntheses of Heterocycles. Molecules 2024, 29, 5265 - Maryna M. Kornet; Thomas J. J. Müller (Molecules)
In the original publication [...]